Physicochemical coastal groundwater dynamics between Kauhakō Crater lake and Kalaupapa settlement, Moloka'i, Hawai'i. (February 2023) - Oberle, Ferdinand K.J.; Cheriton, Olivia M.; Swarzenski, Peter W.; Brown, Eric K.; Storlazzi, Curt D.
Abstract: Land-based sources of groundwater pollution can be a critical threat to coral reefs, and a better understanding of "ridge-to-reef" water movement is required to advance management and coral survival in the Anthropocene. In this study a more complete understanding of the geological, atmospheric, and oceanic drivers behind coastal groundwater exchange on the Kalaupapa peninsula, on Moloka'i, Hawai'i, is obtained by analyzing high resolution geochemical and geophysical time-series data. In concert with multiyear water level analyses, a tidally and precipitation-driven groundwater connection between Kauhakō Crater lake and submarine groundwater discharge (SGD) fluxes are demonstrated. Results include an average discharge rate of 190 cm d −1 and the detection of water-flow pathways past cesspools that likely contribute to higher nutrient loading near the SGD sites. This underlines the importance of managing anthropogenic nutrients that enter the shallow freshwater lens such as through cesspools and are consequently discharged via SGD onto coral reef habitats. Highlights: Kauhakō Crater lake exhibits the world's greatest depth-to-surface area ratio of any lake and is connected to the ocean Mean submarine groundwater discharge rate of 190 cm d − 1 was observed in Kalaupapa Harbor Lidar data and surface observations reveal ephemeral water pathways that flow directly past unregistered cesspools Coastal nutrient loading off Kalaupapa Harbor is associated with focused submarine groundwater discharge